Analisis Ketersediaan Parking Stand Dalam Mencapai On Time Performance (OTP) Di Bandar Udara Kolonel Robert Atty Bessing Malinau - Dyah Nuraliza Pramesthi; Ika Fathin Resti M (Transformasi: Journal of Economics and Business Management, 2024)
Transportation needs will continue to grow over time. One mode of transportation that has many fans is air transportation. Air transportation was chosen because it is a type of transportation that is efficient in terms of time. Airports are a very important factor in supporting the implementation of air transportation activities. With the increase in the number of people's needs, the number of passengers increases so that aircraft movements also increase. The increase that occurs has an impact on On Time Performance. This research uses qualitative methods with resource persons who are members of the Apron Movement Control (AMC) unit. The results of this research show that the available parking stands can fulfill efforts to achieve On Time Performance (OTP). And efforts that can be made by the Apron Movement Control (AMC) unit are to coordinate with related parties such as Ground Handling companies, Airlines, ATS and other units. Apart from that, regular briefings are also carried out to maintain and maintain punctuality of service on the apron.